Rancang Bangun Aplikasi Administrasi Penjualan Pada "CV. Adijaya Elektronik Surabaya" - alfarisi, muhammad fernando; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
ABSTRACT CV . Adijaya Electronics is a company engaged in the sale of spare parts audio. The existing problems in the CV. Electronic Adijaya during the running process of sales administration still use manual way, this causes problems in recording sales transactions, procurement, searches the price of goods, calculation of stock, sales returns, manufacture and sales reports, and memoranda piled up going to lose sales note .              The solution offered is the Design and build a sales administration application that can generate a computerized data and facilitate the implementation of the sales process.Results from the study showed that the application that was created to help sales, procurement, searches the price of goods, calculation of stock, sales returns, manufacturing sales report and assist the needs of users on CV.Adijaya Electronics . Keywords : Applications , administration, sales